Traditional housing in northern Laos - Kretz, Erik (2009)
The majority of the Lao people are living in a mountainous countryside in small villages. The people depend a lot on the forest for a better livelihood. However, in the last decades many changes have occurred in rural Lao, in ways that have ruined large areas of the forest. Laos has lost a little more than 25% of its forests coverage since 1950 and serious forest degradation is widely spread. Slash and burn and uncontrolled logging are the main explanations for deforestation and forest degradation. With an increasing population growth and high economic development there is an increasing need for more forest products. In the forest the local farmers gather and harvest firewood, building materials, medicine, food, and marketable products. However, in the last decades shortages of forest products have been noticed, together with deforestation and fragmentation.